2010
DOI: 10.1007/s11434-009-0591-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of alkali and heat pretreatment on the pathway of hydrogen production from sewage sludge

Abstract: Due to the presence of various types of hydrogen-producing bacteria and numerous organics such as protein and carbohydrate, sewage sludge is a potential material for biological hydrogen production. In this study, two batch tests were carried out to investigate the impact of alkali and heat pretreatment on the pathway of hydrogen production from sewage sludge. The results showed that the heat treatment had a stronger lethal effect on bacteria than the alkali treatment, and could effectively kill hydrogen-consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 37 publications
(32 reference statements)
2
5
0
1
Order By: Relevance
“…Many studies have reported similar results about biohydrogen production of glucose, other carbohydrates and carbohydrate e contained wastes [2]. Although the result of protein was similar with the study conducted by Bai [18] and Akutsu et al [19] in which peptone was also used as the hydrogen-producing substrate, it was not inconsistent with the studies of our previous studies [6,9] and Guo et al [5], in which sludge (a protein-contained waste) was used. The cumulative hydrogen production showed similar increases as the substrate increased, and the cumulative hydrogen production was much higher when glucose was used as the substrate than when protein was used.…”
Section: Hydrogen Fermentations Of Glucose and Protein At Neutral Inisupporting
confidence: 83%
See 3 more Smart Citations
“…Many studies have reported similar results about biohydrogen production of glucose, other carbohydrates and carbohydrate e contained wastes [2]. Although the result of protein was similar with the study conducted by Bai [18] and Akutsu et al [19] in which peptone was also used as the hydrogen-producing substrate, it was not inconsistent with the studies of our previous studies [6,9] and Guo et al [5], in which sludge (a protein-contained waste) was used. The cumulative hydrogen production showed similar increases as the substrate increased, and the cumulative hydrogen production was much higher when glucose was used as the substrate than when protein was used.…”
Section: Hydrogen Fermentations Of Glucose and Protein At Neutral Inisupporting
confidence: 83%
“…While it seemed the short fermentation time (only 58 h) in the test could not completely change the microbial species of sludge but change the dominant microorganisms of sludge. Comparing the results of this study with the studies at alkaline pH for protein and ones at acid pH for glucose [9,27,28], it could be found that the DGGE band numbers of this study were far more than the previous studies, which suggested that these microorganisms in the anaerobic fermentation of this study were more abundant than these previous studies. The abundant microorganisms may be due to the anaerobic fermentation at initial pH was favorable the growth of microorganisms.…”
Section: 4supporting
confidence: 45%
See 2 more Smart Citations
“…Alkaline pretreatment can hydrolyze protein and nucleic acid, damage the enzymes and structures of cells, decompose saccharides, and attack cell walls, releasing intracellular polymers and supplying substrate for sludge fermentation. Wei et al revealed that sludge pretreated with alkali was more suitable for the enrichment of basophilic hydrogen‐producing bacteria. In addition, hydrogen production mainly relied on the fermentation of protein by protein‐utilizing bacteria if sludge was pretreated at alkaline conditions.…”
Section: Sludge Pretreatmentmentioning
confidence: 99%